RUGI-RUGI DAYA PADA TRANSFORMATOR U.019 PT PLN (PERSERO) WS2JB RAYON AMPERA AKIBAT KETIDAKSEIMBANGAN BEBAN - Azis, Abdul; Nurdiana, Nita; Nisa, Ulfa Lathifatun (JURNAL AMPERE, 2018)
Power losses in distribution transformers can cause neutral currents. Neutral currents in distribution transformers can be caused by load imbalances. This study investigates the load imbalance on the secondary side of the transformer U.019 PT. PLN (PERSERO) Palembang Ampera Rayon. Measurement results and calculations show that if a neutral current load is equalized and power losses due to load imbalance in the distribution transformer are reduced. Unbalanced expense loss due to the neutral current of Peak Expense of 41,5090A and the lowest Expense of 12,1244A so that the percentage of loss in Peak Load loss is 5,3443% and the lowest expense is 1,8562%, and due to the falling unbalanced load voltage is obtained Percentage of Peak Loads of 7.28365% and Lowest Load of 2.43736% of balanced load loss due to neutral currents at balanced load, At Peak Load of 4.9482% and afternoon of 1.7647% and due to balanced load voltage drop in Peak can be 4,94819% and the lowest load can be 1,76471%. The load equalization results in the average peak load that is 262.66667 A with the current load current is IR 262A, IS 263A and IT 263A and at the lowest load average current is 95.0000 A, with a perfect load current IR 94 A, IS 95 A and IT 95 A. Difference Between Unbalanced Charges due to neutral currents with a balanced load at peak loads of 3.961% and the lowest load of 915% while the difference in the voltage drop is unbalanced and balanced at peak load 2.33546% and the Lowest Load amounting to 0.67265% ABSTRAK Rugi-rugi daya pada transformator distribusi dapat menimbulkan arus netral. Arus netra lpad atransformator distribusi dapat disebabkan ketidakseimbangan beban. Penelitian ini menyelidiki ketidakseimbangan beban pada sisise kunder transformator U.019 PT. PLN  (PERSERO) Rayon Ampera Palembang. Hasil pengukuran dan perhitungan menunjukkan bahwaapa bila dilakukan pemerataan beban arus netral dan rugi – rugidayaakibatketidakseimbanganbebanpadatransformatordistribusiberkurang.rugi rugi beban ketidak seimbang akibat arus netral Beban Puncak sebesar 41,5090A dan Beban terendah sebesar  12,1244A sehingga persentase rugi rugi daya Beban Puncak sebesar  5,3443% dan beban Terendah 1,8562% ,dan akibat jatuh tegangan beban ketidak seimbang di peroleh persentase pada Beban Puncak  Sebesar 7,28365%  dan Beban Terendah 2,43736% rugi rugi beban seimbang akibat arus netral pada beban seimbang, Pada Beban Puncak sebesar  4,9482% dan siang 1,7647%  dan akibat jatuh tegangan beban seimbang  Benan Puncak  di dapat 4,94819% dan Beban Terendah di dapat  1,76471%. Hasil pemerataan beban di dapat arus rata rata Beban Puncak  yaitu 262,6667 A dengan arus beban perfasa yaitu IR  262A , IS 263A dan  IT  263A dan pada beban Terendah arus rata rata  yaitu 95,0000 A ,dengan arus beban perfasa yaitu IR 94 A , IS 95 A dan  IT 95 A. Selisih Antara Beban Tidak Seimbang akibat arus netral  dengan beban seimbang pada beban puncak sebesar 3,961% dan beban Terendah sebesar 915% sedangkan selisih pada jatuh tegangan tidak seimbang dan seimbang pada beban puncak 2,33546% dan Beban Terendah sebesar 0,67265%